2016
DOI: 10.1002/ajmg.a.37739
|View full text |Cite
|
Sign up to set email alerts
|

Gain‐of‐function mutations in SMAD4 cause a distinctive repertoire of cardiovascular phenotypes in patients with Myhre syndrome

Abstract: Myhre syndrome is a rare, distinctive syndrome due to specific gain‐of‐function mutations in SMAD4. The characteristic phenotype includes short stature, dysmorphic facial features, hearing loss, laryngotracheal anomalies, arthropathy, radiographic defects, intellectual disability, and a more recently appreciated spectrum of cardiovascular defects with a striking fibroproliferative response to surgical intervention. We report four newly described patients with typical features of Myhre syndrome who had (i) a mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 62 publications
2
62
0
1
Order By: Relevance
“…Include 53 cases of the literature reviewed by Lin et al (), the additional cases by Erdem, Sahin, and Tatar () and Garavelli et al () published after Lin et al (), and the current case.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Include 53 cases of the literature reviewed by Lin et al (), the additional cases by Erdem, Sahin, and Tatar () and Garavelli et al () published after Lin et al (), and the current case.…”
Section: Discussionmentioning
confidence: 99%
“…Myhre syndrome (MIM 139210) is a rare autosomal dominant disorder reported so far in over 60 individuals, mostly males diagnosed in childhood or adolescence (Caputo et al, ; Lin et al, ). Clinical features of this disorder include poor growth, variable degree of intellectual disability, distinctive dysmorphic features including short palpebral fissures, maxillary hypoplasia, small mouth with thin upper lip and short philtrum, prognathism, and thick skin.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Papilledema (Erdem, Sahin, & Tatar, 2018) and pseudopapilledema (Al Ageeli et al, 2012;Lin et al, 2016) have also been reported in Myhre syndrome (OMIM 139210), an another acromelic disorder characterized by connective tissue thickening. Unfortunately, the eye findings in these reports are not described in detail and it is thus unclear whether they represent papilledema or pseudopapilledema.…”
mentioning
confidence: 98%